Soliton enhancement cavities - Lilienfein, N.; Högner, M.; Hofer, C.; Saule, T.; Trubetskov, M.; Pervak, V.; Fill, E.; Riek, C.; Leitenstorfer, A.; Limpert, J.; Krausz, F.; Pupeza, I. (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
Femtosecond enhancement cavities (fs-EC), i.e., passive free-space resonators, are commonly used for raising the peak and average power of femtosecond laser pulses to the levels necessary for XUV frequency comb generation via high-order harmonic generation [1] and for augmenting the sensitivity of spectroscopic measurements [2]. Building on previous work on the generation of temporal dissipative Kerr-solitons in fiber- and monolithic microresonators (temporal cavity solitons) [3,4], we demonstrate efficient soliton generation in a fs-EC [5].
CRIS-Team Scopus Importer:2023-04-20